Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1371/journal.pone.0081528
|View full text |Cite
|
Sign up to set email alerts
|

Early Deficits in Glycolysis Are Specific to Striatal Neurons from a Rat Model of Huntington Disease

Abstract: In Huntington disease (HD), there is increasing evidence for a link between mutant huntingtin expression, mitochondrial dysfunction, energetic deficits and neurodegeneration but the precise nature, causes and order of these events remain to be determined. In this work, our objective was to evaluate mitochondrial respiratory function in intact, non-permeabilized, neurons derived from a transgenic rat model for HD compared to their wild type littermates by measuring oxygen consumption rates and extracellular aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 51 publications
(55 reference statements)
4
37
1
Order By: Relevance
“…However, it has also been shown that some mitochondria deficits in HD pathomechanism may only be detected in intact cells [e.g., Gouarné et al (30)]. Our data confirm the assumption as distinct differences in cell respiration and the status of mitochondrial coupling are observed for PC12 HD-Q23 and PC12 HD-Q74 cells when compared to the proper control cells (Figure 2).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, it has also been shown that some mitochondria deficits in HD pathomechanism may only be detected in intact cells [e.g., Gouarné et al (30)]. Our data confirm the assumption as distinct differences in cell respiration and the status of mitochondrial coupling are observed for PC12 HD-Q23 and PC12 HD-Q74 cells when compared to the proper control cells (Figure 2).…”
Section: Discussionsupporting
confidence: 90%
“…However, the role of mitochondria dysfunction is randomly studied in intact cells although the available data highlight the importance of the cellular environment (30). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Olah et al found that the activities of Complexes I–IV in brain mitochondria from 20-week-old transgenic N171-82Q mice were not diminished compared to mitochondria from wild-type animals (Olah et al, 2008). Gouarne et al did not find a difference in respiration of cultured striatal neurons from heterozygous transgenic BACHD rats compared to wild-type neurons, when cells were incubated in the presence of 25 mM glucose and 1 mM pyruvate (Gouarne et al, 2013). In experiments with STHdh Q111/Q111 cells, mitochondrial pathways were not significantly altered and the obtained data uniformly refuted a view of direct deleterious mHtt effect on mitochondria (Lee et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, most of the indications are that parallel metabolic processes also are not optimal. The activity of aconitase, an essential enzyme in the TCA cycle, is significantly decreased in the striatum and cerebral cortex (Tabrizi et al, 1999), GADPH is impaired by faulty autophagy (Hwang et al, 2015), loss of the pyruvate dehydrogenase complex is detected even in asymptomatic patients with caudate/putamen atrophy (Butterworth et al, 1985; Sorbi et al, 1983), glucose uptake is low in HD patients (Pagano et al, 2016), and it is also widely reported that glycolytic rate is reduced in rodent models of HD (Gouarne et al, 2013). …”
Section: Defects In Oxidative Phosphorylation In Human Brainmentioning
confidence: 99%